(untitled) (Journal of Geography and Environmental Management, 2016)
In this article considers the basic socio-demographic indicators of the quality of life in the Almaty region. The main indicators of the quality of social considered: demographic indicators of fertility and mortality, life expectancy of the population, the incidence of the population, the level of education.